How to finance sustainable tourism: Factors influencing the attitude and willingness to pay green taxes among university students - Cristina Ortega-Rodríguez; Julio Vena-Oya; Jesús Barreal; Barbara Józefowicz (Green Finance)
Green taxes are an instrument for the development of many destinations where overtourism generates different externalities, helping to alleviate them and create sustainable tourism. Funds raised through green taxes can be used to finance conservation, environmental restoration, and sustainable development initiatives. However, these taxes are often unknown to tourists visiting a city and can often generate mistrust and even discomfort when they are forced to pay them. In terms of the management implications for destinations, green taxes should be seen and conveyed as a means to achieve both economic and environmental sustainability of destinations and not yet another tax to be borne by the tourist. For this reason, the aim of this study is to explore the factors that affect both the positive attitude and the willingness to pay these taxes. Thus, the opinion about green taxes of 120 university students from different countries were collected to use a structural equation model (SEM) to try to provide answers to the different hypotheses put forward. Young people represent a growing part of the tourism market, shaping the trends and practices of the sector, making them central to the future of tourism. The study seeks to deepen theoretical knowledge on this subject and to provide a series of conclusions and recommendations for education regarding green taxes. In addition, our study on green taxes has a direct relationship with the sustainable development goals promulgated by the United Nations, as both seek to promote balanced economic, social, and environmental development.